People of the spirit: exploring Luke's view of the church - Twelftree, Graham H. (Society for Promoting Christian Knowledge, 2009)
The issues -- Origins and purpose -- Jesus : the church modelled -- Salvation and the church -- The church as the people of God -- Luke's Pentecosts -- The spirit, tongues, and Baptism -- Problems in the early church -- Worship -- Scripture and knowing God -- Experience and knowing God -- Early Ctholic, Protestant, or Charismatic? -- Mission : evangelism or social action or both? -- Listening to Luke